ANALYZING FACTORS DRIVING HOUSE PURCHASE DECISION AT GRIYA PANIKI INDAH MANADO - Anis, Felicia Griselda; Mekel, Peggy; Tumewu, Ferdinand (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
House is one of the important things in human life. Home is where human beings to live, stay, and shelter. Nowadays in North Sulawesi province, especially in particular in the city of Manado, many estates were built. And the most preferred by the people of Manado to buy a house is Griya Paniki Indah. This study aims to analyze the factors that drive consumer purchasing decisions in the house at Griya Paniki Indah Manado. In this study, the population is people who buy a house or are already living in Griya Paniki Indah Manado, with a sample 100 respondents. The method used in this research is a quantitative method by spread the questionnaires to obtain primary data. In this study the results and conclusions found to explain that there are seventeen variables that drive consumers house purchase decision, which then formed the seven factors and there are three variables that do not significantly influence the purchasing decisions in Griya Paniki Indah Manado. The seven factors are customer needs, service level, marketing stimuli, customer satisfaction, word of mouth, views and roads, and personal life. Three variables were not significantly influence the purchasing decisions in Griya Paniki Indah Manado is affordability, maintenance, and affluence. Keywords: consumer purchasing decision